PENGADAAN BAHAN PUSTAKA DI PERPUSTAKAAN MADRASAH TSANAWIYAH AL MUTTAQIN SURABAYA - Fathul Fauzi; Reyhandika Kusnul Kasidi; Nuriya Shofa; M. Iqrom (STAI AN-NAJAH INDONESIA MANDIRI, 2022)
This research concerns the problem of procuring library materials in the library of MTs al muttaqin Surabaya as a case study material. This study aims to identify ways to procure library materials in the MTs al muttaqin Surabaya library so that they can become a reference or reference to find out how to procure these library materials. Starting from how the staff and teachers at the madrasah to fulfill the library materials in the library. This study uses a qualitative method where data collection is carried out by means of interviews and observations so that they are able to dig deeper about how to provide library materials in the MTs Al Muttaqin Surabaya library. The object of this research is a statement from the librarian and other teachers. Procurement of library materials in the library of MTs al Muttaqin Surabaya was mostly obtained from donations from schools that had been occupied by teachers at MTs Al Muttaqin. Not infrequently also obtained from housing donations or residents around the madrasah. Keywords: Procurement, library materials, library References Murnahayati,Pengadaan Bahan Pustaka pada Perpustakaan Fakultas Syariab UIN Imam Bonjol Padang. Bafadal, Ibrahim. (2011). Pengelolaan Perpustakaan Sekolah. Jakarta: Bumi. Aksara. Soetminah. Perpustakaan Pustakawan dan Kepustakawanan. Yoyakarta: Kanisius, 1992 Solistyo-Basuki. Pengantar Ilmu Perpustakaan. Jakarta: Gramedia Pustaka Utama, 1991 Wiji Suwarno, Dasar-dasar Ilmu Perpustakaan, (Yogyakarta: Ar-Ruzz Media, 2014) Mujamil Qomar, Strategi Pendidikan Islam, (Jakarta : Erlangga 2013)